Fungicides with physiological effects on the formation of grafted tomato seedlings - Amaro, Amanda Cristina Esteves [UNESP]; Baron, Daniel; Ramos, Anamaria Ribeiro Pereira [UNESP]; Rodrigues, João Domingos [UNESP]; Ono, Elizabeth Orika [UNESP] (Southern Cross Publishing, 2018)
In tomato, grafting is being used as a preventive measurement of diseases control. During the grafting process, plants tend to overproduce reactive oxygen species in response to injury, controlling oxidative stress. It may be an important factor in achieving success in grafting. The present work aimed to evaluate if the before and after grafting application of pyraclostrobin and boscalid improves the activity of antioxidant enzymes and photosynthetic pigments, resulting in growth improvement of grafted tomato plants during graft union formation. The experimental design was in randomized blocks, with 7 treatments such as: control; pyraclostrobin 0.15 g L-1; boscalid 0.15 g L-1; pyraclostrobin 0.15 g L-1+boscalid 0.15 g L-1; pyraclostrobin 0.25g L-1; boscalid 0.25g L-1; pyraclostrobin 0.25 g L-1+boscalid 0.25 g L-1 in 6 replicates. These treatments were applied to the substrate, at sowing of the scion and rootstock and through foliar application 20 days after sowing and 4 days after grafting (DAG). The 'Pizzadoro' tomato plants were grafted onto 'Guardian', 30 days after sowing, using the splice grafting method. The antioxidant enzymes activities were evaluated at the hypocotyl region, and lipid peroxidation and photosynthetic pigments at leaves at 2, 8 and 14 DAG. Plant growth was evaluated at 2 and 14 DAG. Treatment with fungicides improved the physiological performance of the seedlings, increasing the relative growth rate. The results suggest that the preventive application of pyraclostrobin and boscalid is responsible for inducing the efficiency of the antioxidative system and the concentration of photosynthetic pigments in grafted tomato plants, contributing to the reestablishment of these plants.
Keywords: Antioxidant enzymes; Carboxamide; Grafting; Solanum lycopersicum; Strobilurin